COVID-19 pandemic and nursing week: analysis from software Iramuteq - Samira Silva Santos Soares; Norma Valéria Dantas de Oliveira Souza; Eloá Carneiro Carvalho; Ana Beatriz Azevedo Queiroz; Carolina Cabral Pereira da Costa; Jaqueline da Silva Soares Souto
ABSTRACT Objective: to analyze the themes of publications on the Federal Council of Nursing (Cofen) website during Nursing Week 2020. Method: documentary, qualitative research, whose data sources were publications on the Cofen website from May 12 to 20, 2020. Data were processed by software IRAMUTEQ®, through the Descending Hierarchical Classification and analyzed under the historical materialism framework. Results: thirty publications were analyzed, giving rise to five classes. Final considerations: the themes published in the period investigated pointed to the grief experienced by the category, due to the death of its members, and the fight for better working conditions. Overcoming the pandemic involves recognizing science and the Unified Health System, protecting nursing workers' health and fighting misinformation and fake news.